Juridical Analysis of Law Enforcement Against Criminal Acts of Bullying Victimization in Schools - Iryani, Hera; Adi Surya G.S., Achmad; Yestati, Ariani (Journal of Law, Politic and Humanities, 2025)
Bullying against children constitutes a form of violence that frequently occurs within educational institutions and has serious consequences for victims’ physical, psychological, and social well-being. Bullying may arise from various factors, including family dynamics, school environment, peer influence, and social media. As the guarantor of children's rights, the State bears legal responsibility to ensure children's safety and welfare within educational settings. This research employs a normative juridical method, relying on statutory, doctrinal, and secondary legal materials. The core focus of the study is a legal analysis of the enforcement of protections for victims of bullying in educational institutions in the City of Palangka Raya, pursuant to Law Number 35 of 2014 on Child Protection and the Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 46 of 2023 concerning the Prevention and Handling of Violence in Educational Units. Findings indicate that although the legal framework is clearly established, implementation remains hindered by challenges such as public unawareness and the limited availability of early detection mechanisms. Accordingly, an active role from schools, parents, and collaboration with law enforcement is essential to ensure effective legal protection for victims